How Elite Partisan Polarization Affects Public Opinion Formation - DRUCKMAN, JAMES N.; PETERSON, ERIK; SLOTHUUS, RUNE (The American political science review, 2013)
Competition is a defining element of democracy. One of the most noteworthy events over the last quarter-century in U.S. politics is the change in the nature of elite party competition: The parties have become increasingly polarized. Scholars and pundits actively debate how these elite patterns influence polarization among the public (e.g., have citizens also become more ideologically polarized?). Yet, few have addressed what we see as perhaps more fundamental questions: Has elite polarization altered the way citizens arrive at their policy opinions in the first place and, if so, in what ways? We address these questions with a theory and two survey experiments (on the issues of drilling and immigration). We find stark evidence that polarized environments fundamentally change how citizens make decisions. Specifically, polarization intensifies the impact of party endorsements on opinions, decreases the impact of substantive information and, perhaps ironically, stimulates greater confidence in those—less substantively grounded—opinions. We discuss the implications for public opinion formation and the nature of democratic competition.